Climate change policy implementation in Buenos Aires (2015-2020) - Yáñez, Daniela Mariana (Iberoamerican Journal of Development Studies, 2023)
In a world where climate change has been one of the main challenges in the last decades, cities and local governments are key players to mitigate greenhouse gas emissions and adapt to new climate conditions. This article focuses on climate change policy implementation at local level. Using the city of Buenos Aires as a case study, in this research it is aimed to identify which micro- and macro-level factors and the context enable the local government to implement its climate change action plan launched in 2015. To do so, Ryan’s framework is used. The main findings of this paper support the hypothesis tested: Buenos Aires local government had sufficient resources and support from political and social coalitions, as well as the ability to link climate action with local issues to implement the Climate Change Action Plan (2015-2020).
Keywords: climate change; policy implementation; local government; Buenos Aires